Corporate Governance’s Role in the Risk-Return Paradox - New Evidence from Indian Firms - Ranjan Dasgupta (Australasian Accounting, Business and Finance Journal, 2021)
Prior empirical research emphasises ‘troubled’ firm context and ‘quality management’ perspective as reasons for a ‘paradoxical’ or negative risk-return association for firms. But, to the best of our knowledge, no studies examine the role of individual corporate governance mechanisms in influencing such a ‘paradox’. Therefore, the study investigates this issue by classifying 675 sample Indian firms over the period 2000-2017 into high performing and low performing firms in line with the strategic reference point theory and the behavioural theory. To fulfil study objectives, it uses four different firm-return measures and estimate firm-level risk with standard deviations of each return measures previous 5 years’ values on a rolling basis. In the univariate model, the study uses the notion of target (reference) return level under firm’s own and social aspiration levels in time-variant and market cycles contexts, and then compute Kendall’s correlations in between distance from such targets and their standard deviations. The study also carries out a multivariate regression model with necessary controls to further validate its univariate findings. The study results report significant influential role that board size and women directors’ presence play in both high and low performing firms’ ‘paradoxical’ risk-return association. On the contrary, board meetings, busy board and board tenure develops a risk-return ‘paradox’ for high performing firms only. These results hold true across my return measures, strategic reference points, market cycles and corporate governance regimes after controlling for firm- and industry-level heterogeneities under both univariate and multivariate analyses.
Keywords: Risk-return paradox; Corporate governance; Reference point; Aspiration level; Firm-risk and -return measures.